Ecotourism and geotourism in Ukraine - Marta Malska; Yurii Zinko; Nataliia Antoniuk (Journal of Geography, Politics and Society, 2016)
Cognitive nature tourism in Ukraine has a long tradition of development. Today, ecotourism, active forms of tourism, ethnographic trips and trips to historical and cultural destinations are mostly developed. The most popular offers come from national parks and other natural areas with preserved natural, historical and cultural environments. Among the regions with active forms of tourism, the Carpathian mountain region and the Crimea with a well-developed network of hiking and biking trails should be noted. Rafting on the Black Cheremosh, Prut, Southern Bug, Dniester, Desna, Sluch, Teteriv and other rivers is quite popular as well as trips to caves (in Podillia, the Carpathians and the Crimea), which are often combined with visits to other natural attractions. Travel agencies, specialized clubs, national parks and nature reserves, which cooperate to promote their offers on domestic and international tourist market, organize informative trips.